Obesity and Sleep-Related Breathing Disorders in Middle East and UAE - Mayank G. Vats; Bassam H. Mahboub; Hassan Al Hariri; Ashraf Al Zaabi; Deepa Vats (Canadian Respiratory Journal)
A pandemic of obesity is sweeping all across the globe and the Middle East region also does not remain untouched by this prevailing pandemic. In fact, as per WHO report, Kuwait has the second highest obesity prevalence followed closely by other Middle East (ME) countries, namely, Qatar, Saudi Arabia, and United Arab Emirates (UAE). Apart from direct medical, psychological, and quality of life related adverse effects of obesity, many indirect medical comorbidities, namely, obstructive sleep apnea (OSA), obesity hypoventilation syndrome (OHS), diabetes mellitus (DM), hypertension (HTN), and metabolic syndrome, imposes a significant health burden on the individual and community with consequent morbidity and mortality. The purpose of this review is to shed light on the very high prevalence of obesity, undiagnosed sleep apnea, and other obesity related disorders with discussion of the contributing factors specific to the region including the fair insight into the current status of sleep medicine services in Middle East and UAE despite huge number of patients having undiagnosed sleep disorders. We will also suggest to control this epidemic of obesity and OSA so that the corrective measure could be taken at health ministry level to help people of this region to fight against obesity and related disorders, primarily OSA.